Crop diversification, land price spillovers, and land governance: evidence from China - Liu, Yu; Wang, Shangao; Zhu, Honggen; Wang, Yue (Frontiers in Sustainable Food Systems, 2024)
Introduction Crop diversification from grain to non-grain production is often considered a threat to food security in many populous countries with limited arable land. Yet its potential spillover effect has not been fully studied. This study explores a unique plot-level dataset to particularly quantify the spillover effect of non-grain production on the land rental price of grain production from the perspective of factor opportunity cost and proposes corresponding land management strategies. Methods Data used in this study came from a field survey conducted in Jiangsu province. OLS method was employed to test the effect of non-grain production on the rent price of grain production farmland, combined with plot-level heterogeneity analysis. In addition, Quantile method was used for robustness check. Results Our main finding indicates that converting land use from grain production to non-grain production significantly increases the land rental rate of surrounding plots for grain production by 222.02 yuan/mu, accounting for 28.75% of the total land rent (772.25 yuan/mu). This spillover effect exhibits a stronger trend as the contracted land scale expands. However, the kin relationship among contract parties can weaken this effect, indicating that social ties can work as a mediator in offsetting the negative shock of the rental rate increase due to non-grain production. In order to keep the land rent under control, rural land use is actively harnessed by local governments at a guided price. Discussion Based on the empirical results, the study recommends comprehensive land use planning and a regionally regulated land transfer market in order to achieve a balance between food security and a diversified agricultural structure.